Dimensi Teks dalam Analisis Wacana Kritis Teun A. Van Dijk pada Pemberitaan Keracunan MBG di Projectmultatuli.org - Mochamad Alwi Safarudin; Ali Alamsyah Kusumadinata; Agustini Agustini (Institut Nalanda, 2026)
The Free Nutritious Meal Program (MBG) is one of the government policies aimed at fulfilling the nutritional needs of school children. However, in its implementation, cases of mass food poisoning emerged and raised criticism regarding the state’s responsibility in ensuring food safety. This study aims to analyze how the text dimension in ProjectMultatuli.org news constructs discourse regarding the food poisoning cases in the Free Nutritious Meal Program using Teun A. Van Dijk’s Critical Discourse Analysis approach. This research employs a descriptive qualitative method with the object of study being the news article entitled “Keracunan Nasional MBG: Anak-Anak Membayar Mahal Kelalaian Negara” published in September 2025. The analysis focuses on the text dimension which includes macrostructure, superstructure, and microstructure. The results show that ProjectMultatuli.org constructs a critical discourse by positioning the state as the responsible party for the mass poisoning incident through the emphasis on the theme of state negligence, systematic news scheme arrangement, and the use of semantic, syntactic, stylistic, and rhetorical elements that strengthen the position of victims as the disadvantaged party. The novelty of this study lies in its focus on the text dimension analysis of MBG food poisoning coverage, which is still rarely discussed in communication studies, particularly in public service journalism media such as Project Multatuli.